Association of Aldosterone, Plasma Renin Activity (PRA) and Superoxide Dismutase (SOD) with Inflammation and Insulin Resistance in Adult Men with Central Obesity - Hera Yuliana Intantri; Andi Wijaya; Ilhamjaya Patellongi (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Visceral Obesity is related with chronic low grade inflammation, and is the main component of metabolic syndrome (MetS). MetS is associated with increased cardiovascular disease (CVD). Furthermore, superoxide dismutase (SOD) is correlated with insulin resistance. Several studies have reported a strong correlation between Renin Angiotensin Aldosterone System (RAAS) and CVD, but the association of Aldosterone, Plasma Renin Activity (PRA) and SOD with inflammation, insulin resistance and MetS have not been fully elucidated. The aim of this study was to investigate the correlation of Aldosterone, PRA, and SOD with inflammation (high sensitivity c-reactive protein/hsCRP) and insulin resistance (homeostasis model assessment-insulin resistance/HOMA-IR) in adult men with central obesity.METHODS: This was a cross-sectional study, which was carried out on 80 male subjects with central obesity who were divided into 2 groups: the group of subjects who had fulfilled the MetS criteria and the other group of subjects who did not. After an overnight fasting, blood pressure (BP) was measured on all subjects and laboratory examinations were done for measurement of the concentration of fasting glucose, high density lipoprotein cholesterol (HDL-C), triglyceride, hsCRP, insulin, aldosterone, PRA, and SOD.RESULTS: We found aldosterone had positive correlation with PRA (r = 0.389; p < 0.001) and triglycerides (r =0.234; p=0.036). PRA had positive correlation with SOD (r=0.220; p=0.05) and HDL-C (r=0.273; p=0.014), but not with hsCRP (r=-0.044; p=0.696) and HOMA-IR (r=0.168 p=0.136). PRA correlated with HOMA-IR in MetS (r=0.471; p=0.01). Aldosterone and PRA were correlated with diastolic pressure in those with hypertension (r=0.680; p=0.003 and r=0.608; p=0.01).CONCLUSIONS: There is no direct correlation between aldosterone or SOD and Insulin resistance, and inflammation in men with central obesity. The correlation between PRA and MetS might be through insulin resistance mechanism. We found significant correlation between PRA, HDL-C and SOD. Increased aldosterone was ccorrelated with elevated triglycerides, thus possibly increasing the risk of MetS.KEYWORDS: central obesity, aldosterone, plasma renin activity, superoxide dismutase, inflammation, insulin resistance